The Warburg effect in mycobacterial granulomas is dependent on the recruitment and activation of macrophages by interferon-γ - Appelberg, Rui (2015)
Granulomas are the hallmark of mycobacterial disease. Here, we demonstrate that both the cell recruitment and the increased glucose consumption in granulomatous infiltrates during Mycobacterium avium infection are highly dependent on interferon-y (IFN-y). Mycobacterium avium-infected mice lacking IFN-y signalling failed to developed significant inflammatory infiltrations and lacked the characteristic uptake of the glucose analogue fluorine-18-fluorodeoxyglucose (FDG). To assess the role of macrophages in glucose uptake we infected mice with a selective impairment of IFN-y signalling in the macrophage lineage (MIIG mice). Although only a partial reduction of the granulomatous areas was observed in infected MIIG mice, the insensitivity of macrophages to IFN-y reduced the accumulation of FDG. In vivo, ex vivo and in vitro assays showed that macrophage activated by IFN-y displayed increased rates of glucose uptake and in vitro studies showed also that they had increased lactate production and increased expression of key glycolytic enzymes. Overall, our results show that the activation of macrophages by IFN-y is responsible for the Warburg effect observed in organs infected with M. avium.